EVALUATION OF PATIENT SATISFACTION OF HOSPITALIZED SERVICES AFTER HEALTH SYSTEM EVOLUTION PLAN IN THE FIELD OF TREATMENT IN IRAN - Karami, Z.; Haghighat, S.; Ganji, H.; Yazdannik, A. (University of Eloued جامعة الوادي, 2018)
Satisfaction of patients is so important that the WHO is one of the five indicators of quality of health services and is one of the main indicators of the effectiveness of the health system. The aim of this study was to determine the satisfaction of patients following the implementation of the Health System Development Plan Not. Methods: This is a cross-sectional descriptive study that was conducted in the emergency department of Al-Zahra University of Medical Sciences from November 2016 to June 2017. 200 patients over 18 years old, 24 hours after admission, with stable physical conditions , Had the ability to read and write, lack of mental disorders, physical-mental disabilities and being cleared by available sampling method. Patients who were ill, unsatisfied and confused questionnaires were excluded from the study. Satisfaction of patients was collected by interview using a questionnaire. Data were analyzed using descriptive and inferential statistics in SPSS 19 software. Results:Patients' satisfaction with the health system development plan was 56.3%, 47.4%, physical environment 58.4%, drug delivery 76.6%, and unofficial payment Physicians 41.6% and satisfaction of doctors, nurses and the therapeutic team were 59.5%, 58.3%, and 57.7% respectively. The total satisfaction score of patients from the health system development plan was 57 ± 18.1. The total satisfaction score of patients with their hospital stay was directly related (P = 0.02). Conclusion: According to the results of this study, the most satisfaction with the availability of drugs was 76.6%, and the least of them was due to the unofficial payment and unofficial payments to doctors with 41.6%. Therefore, the implementation of the Health System Development Plan has been able to increase the degree of satisfaction of patients.
Article in Journal of Fundamental and sciences. university of el oued
Keywords: Satisfaction, Health System Reform, Patients, Iran